Factors associated with seclusion and restraint on admission to forensic psychiatric hospitals: A 10-year retrospective study - Elke Ham; Soyeon Kim; N. Zoe Hilton (PLoS ONE, 2025)
The use of coercive measures such as seclusion and restraint in forensic mental healthcare settings is widespread but controversial. Efforts to reduce these measures require knowledge of patient-related risk factors. The present study aimed to identify and confirm factors related to seclusion and restraint that can be assessed upon admission among men and women admitted to forensic hospitals in Ontario, Canada. We included cross-sectional Ontario Mental Health Reporting System admission data for adult patients admitted to 10 forensic psychiatric hospitals between April 1, 2013, and March 31, 2023. We determined patient demographic, administrative, and clinical characteristics associated with seclusion and physical and manual restraint episodes during the first three days of admission. We conducted logistic Generalized Linear mixed Models (GLMM) to examine the association between the independent variables and restraint and seclusion while accounting for variability across facilities. Of 7635 patients, 30.2% (n = 2302) were secluded, and 3.7% (n = 286) were restrained within their first three days of admission. Secluded patients were more likely to be young adults, male, and scored higher on violence and aggression measures. Being admitted due to fitness-related reasons, lack of insight, medication non-adherence, higher scores on the mania scale and cognitive impairment further contributed to the higher odds of being secluded, whereas neurocognitive disorder diagnosis and elopement behavior were protective factors. Restrained patients were also more likely to be young adults, have a diagnosis of mood or anxiety, neurodevelopmental or personality disorder, and scored higher on violence and aggression measures. Fitness-related status, medication non-adherence, and cognitive impairment further contributed to this model of restraint. Indigenous self-identification and immigration status were not significant contributors to either model. Clinicians can assess indicators associated with seclusion and restraint when forensic patients are admitted to forensic hospitals or during the first three days of their stay, enabling effective targeting of those needs to reduce the use of coercive measures.